High-wettability fiber composite battery diaphragm and preparation method thereof

By adding high wetting fibers, ceramic powders and binders to the battery separator coating, the problem of insufficient wetting properties of traditional separator coatings is solved, and the ion transmission efficiency and overall performance of the battery are significantly improved.

CN119447700APending Publication Date: 2025-02-14WUXI ENERGY NEW MATERIALS TECH CO LTD
View PDF 0 Cites 2 Cited by

Patent Information

Application Number
CN202411597602.X
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-11
Publication Date
2025-02-14

AI Technical Summary

Technical Problem

The ceramic coating of traditional battery separators has poor wetting properties, resulting in limited contact area between the electrolyte and the separator, limiting the improvement of battery performance.

Method used

A highly wettable fiber composite battery separator is used, and its coating contains highly wettable polymer nanofibers, ceramic powders and binders. Through the combination and treatment of these components, the wettability of the separator is significantly improved.

Benefits of technology

By improving the wettability of the separator, the contact area between the electrolyte and the separator is increased, the ion transmission efficiency of the battery is improved, and the overall performance of the battery is improved.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119447700A_ABST
    Figure CN119447700A_ABST
Patent Text Reader

Abstract

The invention provides a high-wettability fiber composite battery diaphragm, which is characterized in that the composite battery diaphragm comprises a base membrane and a coating, and the coating is coated on one side or two sides of the base membrane; the coating comprises high-wettability polymer nanofibers, ceramic powder and a binder, the single-side thickness of the coating is 0.5-4 [mu] m, the high-wettability polymer nanofibers have polar functional groups, and the binder fixes the ceramic powder and the high-wettability nanofibers on the base membrane; the base membrane comprises at least one of a polyethylene microporous membrane, a polypropylene microporous membrane and a polypropylene / polyethylene composite microporous membrane, and the thickness of the base membrane is 3-20 microns. By adding the fibers with excellent wettability and the ceramic powder with high chemical stability, the wettability of the diaphragm coating is improved, and the battery performance is improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application relates to the technical field of battery manufacturing, and in particular to an improved method for battery separator coating, in which the wettability of the separator is improved by adding fibers with high wettability. Background Art

[0002] At present, the performance of battery separators, as key components to prevent short circuits between positive and negative electrodes, directly affects the overall performance of the battery. Among them, the wettability of the separator coating is an important factor affecting the ion transfer efficiency and battery performance. The ceramic coating of traditional separators often has poor wettability, resulting in limited contact area between the electrolyte and the separator, thus limiting the performance improvement of the battery. Therefore, developing a method that can significantly improve the wettability of the separator coating has become an important research direction in the current field of battery technology. Summary of the invention

[0003] Therefore, the main purpose of the present application is to provide a high wettability fiber composite battery separator and a preparation method thereof, so as to further optimize the above-mentioned problems.

[0004] In order to solve the above-mentioned technical problems, the purpose of the present application is to provide a high wettability fiber composite battery separator, characterized in that the composite battery separator includes a base film and a coating, and the coating is applied to any one side or both sides of the base film; the coating contains high wettability polymer nanofibers, ceramic powder and a binder, and its single-side thickness is 0.5μm to 4μm; the high wettability polymer nanofibers have polar functional groups, and the binder fixes the ceramic powder and the high wettability nanofibers on the base film; the base film includes at least one of a polyethylene microporous membrane, a polypropylene microporous membrane, and a polypropylene / polyethylene composite microporous membrane, and its thickness is 3μm to 20μm.

[0005] As described above, the high wettability fiber composite battery separator, wherein the coating comprises a single layer or a double layer, wherein each layer comprises the same or different high wettability polymer nanofibers, the ceramic powder and the binder.

[0006] As described above, the high wettability fiber composite battery separator, wherein the high wettability polymer nanofiber comprises at least one of aramid fiber, polytetrafluoroethylene fiber, polyimide fiber, cellulose nanofiber, and polyacrylonitrile nanofiber.

[0007] As described above, the high wettability fiber composite battery separator, wherein the diameter of the high wettability polymer nanofiber is 20nm to 1000nm, and the length is 2μm to 100μm.

[0008] The high wettability fiber composite battery separator as described above, wherein the aspect ratio of the high wettability polymer nanofiber is 2 to 5000.

[0009] As described above, the high wettability fiber composite battery separator, wherein the ceramic powder contains at least one of alumina, boehmite, barium titanate, barium sulfate, silicon dioxide, titanium dioxide, magnesium oxide, aluminum hydroxide, magnesium hydroxide, silicon nitride, and silicon carbide.

[0010] As described above, in the high wettability fiber composite battery separator, the particle size D50 of the ceramic powder is 0.05 μm to 3 μm.

[0011] As described above, the high wettability fiber composite battery separator, wherein the high wettability polymer nanofiber contains at least one group selected from the group consisting of cyano (-CN), ester (-COOR), ether (-OR), carboxyl (-COOH), amino (-NH2), sulfonic acid (-SO3H), acetyl (-COCH3), sulfonyl (-SO2-), pyridine (-C5H5N), aldehyde (-CHO), thienyl (-C4H3S), nitrile (-C≡N), alkoxy (-OCH2-), and phosphate (-PO4), so that polar functional groups that are pro-electrolyte are formed on the surface of the high wettability nanofiber.

[0012] The high wettability fiber composite battery separator as described above, wherein the weight ratio of the high wettability polymer nanofibers to the ceramic powder is (1 to 40):(99 to 60).

[0013] As described above, in the high wettability fiber composite battery separator, the binder comprises at least one of polyvinylidene fluoride, polytetrafluoroethylene, polyvinyl alcohol, polyacrylic acid, polyacrylonitrile and polymethyl methacrylate.

[0014] Another object of the present application is to provide a method for preparing a high wettability fiber composite battery separator, characterized in that it includes the following steps: a dispersant aqueous solution preparation step: adding the dispersant into deionized water, stirring thoroughly to obtain a dispersant aqueous solution; a fiber powder aqueous solution formation step: adding nanofibers and ceramic powders into the dispersant aqueous solution and continuing to stir, and then adding them into a homogenizer for dispersion to obtain a fiber powder aqueous solution, wherein the high wettability polymer nanofibers have polar functional groups; a coating slurry preparation step: adding a binder, a thickener, and a wetting agent into the fiber powder aqueous solution, stirring evenly, and then performing demagnetization filtration to obtain the coating slurry; and a slurry coating step: applying the coating slurry to a base film, and then drying to obtain a high wettability fiber composite battery separator.

[0015] The method for preparing a high wettability fiber composite battery separator as described above, wherein, in the step of preparing the dispersant aqueous solution, the dispersant contains at least one of polyethylene, polyethylene glycol, sodium polyacrylate, ammonium polyacrylate, and sodium hexametaphosphate.

[0016] The method for preparing a high wettability fiber composite battery separator as described above, wherein, in the step of forming the fiber powder aqueous solution, the high wettability polymer nanofiber comprises at least one of aramid fiber, polytetrafluoroethylene fiber, polyimide fiber, cellulose nanofiber, and polyacrylonitrile nanofiber.

[0017] The method for preparing a high wettability fiber composite battery separator as described above, wherein, in the step of forming the fiber powder aqueous solution, the ceramic powder contains at least one of aluminum oxide, boehmite, barium titanate, barium sulfate, silicon dioxide, titanium dioxide, magnesium oxide, aluminum hydroxide, magnesium hydroxide, silicon nitride, and silicon carbide.

[0018] As described above, in the method for preparing a high wettability fiber composite battery separator, in the step of forming the fiber powder aqueous solution, the total solid content of the ceramic powder and the high wettability polymer nanofibers in the fiber powder aqueous solution is 20wt% to 50wt%.

[0019] The method for preparing a high wettability fiber composite battery separator as described above, wherein, in the coating slurry preparation step, the thickener comprises at least one of sodium carboxymethyl cellulose, methyl cellulose, hydroxypropyl methyl cellulose, and carbopol resin.

[0020] The method for preparing a high wettability fiber composite battery separator as described above, wherein, in the coating slurry preparation step, the wetting agent comprises at least one of organically modified silicones, polyols, and fatty alcohol ethers.

[0021] The method for preparing a high wettability fiber composite battery separator as described above, wherein, in the coating slurry preparation step, the binder comprises at least one of polyvinylidene fluoride, polytetrafluoroethylene, polyvinyl alcohol, polyacrylic acid, polyacrylonitrile, and polymethyl methacrylate.

[0022] The purpose of the present invention is to provide a method for preparing a battery diaphragm coating reinforced with a composite of high wettability fibers and ceramic powders, which improves the wettability of the diaphragm coating and improves battery performance by adding fibers with excellent wettability and ceramic powders with high chemical stability. BRIEF DESCRIPTION OF THE DRAWINGS

[0023] Figure 1 This is a SEM of the coating surface of a high wettability fiber composite battery separator according to an embodiment of the present application.

[0024] Figure 2This is a schematic block diagram of a process for preparing a high wettability fiber composite battery separator according to an embodiment of the present application. DETAILED DESCRIPTION

[0025] The following descriptions of the embodiments refer to the attached drawings to illustrate specific embodiments that can be implemented in the present application. Directional terms mentioned in the present application, such as "upper", "lower", "front", "back", "left", "right", "inner", "outer", "side", etc., are only referenced to the directions of the attached drawings. Therefore, the directional terms used are used to illustrate and understand the present application, but are not used to limit the present application.

[0026] The accompanying drawings and descriptions are considered to be illustrative in nature and not restrictive. In the drawings, units with similar structures are represented by the same reference numerals. In addition, for the sake of understanding and ease of description, the size and thickness of each component shown in the drawings are arbitrarily shown, but the application is not limited thereto.

[0027] In the drawings, the thickness of layers, films, regions, etc. are exaggerated for clarity. In the drawings, the thickness of some layers and regions are exaggerated for understanding and ease of description. It will be understood that when a component such as a layer, film, region, or substrate is referred to as being "on" another component, the component may be directly on the other component, or intermediate components may also be present.

[0028] In addition, in the specification, unless explicitly described to the contrary, the word "comprising" will be understood to mean including the components, but not excluding any other components. In addition, in the specification, "on" means being located above or below the target component, and does not mean necessarily being located on the top based on the direction of gravity.

[0029] In order to further explain the technical means and effects adopted by the present application to achieve the predetermined invention purpose, the following, in combination with the drawings and specific embodiments, a high wettability fiber composite battery separator and its preparation method proposed in the present application, its specific implementation method, structure, characteristics and effects are described in detail as follows.

[0030] A high wettability fiber composite battery separator according to an embodiment of the present application is characterized in that the composite battery separator comprises a base film and a coating, wherein the coating is applied on one side or both sides of the base film, and the SEM of the coating surface is as follows: Figure 1As shown; the coating comprises high wettability polymer nanofibers, ceramic powder and a binder, and its single-side thickness is 0.5μm to 4μm; that is, when the coating is applied to one side of the base film, the total thickness of the coating is 0.5μm to 4μm; when the coating is applied to both sides of the base film, the total thickness of the coating is 1μm to 8μm; the high wettability polymer nanofibers have polar functional groups; the binder fixes the ceramic powder and the high wettability nanofibers on the base film; the base film comprises at least one of a polyethylene microporous membrane, a polypropylene microporous membrane, and a polypropylene / polyethylene composite microporous membrane, and its thickness is 3μm to 20μm.

[0031] In some embodiments, the coating comprises a single layer or a double layer, wherein each layer comprises the same or different high wettability polymer nanofibers, the ceramic powder and the binder. Specifically, when the coating comprises a double layer, the double layer can be formed simultaneously on the same side of the base film or on both sides. The high wettability polymer nanofibers comprise at least one of aramid fibers, polytetrafluoroethylene fibers, polyimide fibers, cellulose nanofibers and polyacrylonitrile nanofibers. The diameter of the high wettability polymer nanofibers is 20nm to 1000nm, and the length is 2μm to 100μm; the diameter is preferably 100nm to 1000nm, and the length is preferably 5μm to 80μm. The aspect ratio of the high wettability polymer nanofibers is 2 to 5000; the aspect ratio is preferably 5 to 800; the aspect ratio is more preferably 10 to 600; the aspect ratio is more preferably 50 to 120; the aspect ratio is also preferably 80 to 100. The ceramic powder comprises at least one of alumina, boehmite, barium titanate, barium sulfate, silicon dioxide, titanium dioxide, magnesium oxide, aluminum hydroxide, magnesium hydroxide, silicon nitride, and silicon carbide. The particle size D50 of the ceramic powder is 0.05 μm to 3 μm; the particle size D50 is preferably 0.1 μm to 0.8 μm. The binder is at least one of polyvinylidene fluoride, polytetrafluoroethylene, polyvinyl alcohol, polyacrylic acid, polyacrylonitrile, and polymethyl methacrylate.

[0032] In some embodiments, the high wettability polymer nanofiber contains at least one group selected from cyano (-CN), ester (-COOR), ether (-OR), carboxyl (-COOH), amino (-NH2), sulfonic acid (-SO3H), acetyl (-COCH3), sulfonyl (-SO2-), pyridyl (-C5H5N), aldehyde (-CHO), thienyl (-C4H3S), nitrile (-C≡N), alkoxy (-OCH2-), phosphate (-PO4), etc., so that polar functional groups that are pro-electrolyte are formed on the surface of the high wettability nanofiber, and the polar functional groups interact with the ions in the electrolyte to reduce the interface resistance and improve the ion conduction efficiency. In some embodiments, the weight ratio of the high wettability polymer nanofiber to the ceramic powder is (1 to 40): (99 to 60). Preferably, the thickness of the high wettability fiber composite battery separator is less than 20 μm.

[0033] See also Figure 2 In some embodiments, the present application provides a method 1 for preparing a fiber composite battery separator with high wettability, characterized in that it comprises the following steps: a dispersant aqueous solution preparation step S11: adding the dispersant into deionized water, stirring it thoroughly to obtain a dispersant aqueous solution; a fiber powder aqueous solution formation step S12: sequentially adding nanofibers and ceramic powders into the dispersant aqueous solution and continuing stirring, and then adding them into a homogenizer for dispersion to obtain a fiber powder aqueous solution; a coating slurry preparation step S13: sequentially adding a binder, a thickener, and a wetting agent into the fiber powder aqueous solution, stirring evenly, and then performing demagnetization filtration to obtain the coating slurry; and a slurry coating step S14: applying the coating slurry to a base film, and then drying it to obtain a fiber composite battery separator with high wettability.

[0034] In this embodiment, the slurry preparation method provided is implemented at room temperature, is simple to operate, and is easy to scale up. The high wettability fiber composite battery separator comprises a base film and a coating. The SEM image of the coating surface is as follows: Figure 1 As shown. In some embodiments, the base film used is a polyethylene microporous film, a polypropylene microporous film, a polypropylene / polyethylene composite microporous film, with a thickness of 3 μm to 20 μm and an air permeability of 70s / 100cc to 300s / 100cc. In some embodiments, the single-side thickness of the coating is 0.5 μm to 7 μm, and the coating can also be coated on both sides of the base film; the mass ratio of the high wettability polymer nanofibers to the ceramic powder is preferably (3 to 30): (97 to 70). The cost of high wettability polymer nanofibers is much higher than that of ceramic powders, and the high wettability polymer nanofiber content is too high, which is not conducive to reducing the cost of large-scale production.

[0035] In some embodiments, the ceramic powder is at least one of alumina, boehmite, barium titanate, barium sulfate, silicon dioxide, titanium dioxide, magnesium oxide, aluminum hydroxide, magnesium hydroxide, silicon nitride, and silicon carbide; the particle size D50 is 0.05 μm to 3 μm, and the particle size D50 is preferably 0.1 μm to 0.8 μm. In some embodiments, the high wettability polymer nanofiber is at least one of aramid fiber, polytetrafluoroethylene fiber, polyimide fiber, cellulose nanofiber, and polyacrylonitrile nanofiber; the fiber is modified with carboxyl or hydroxyl groups; the diameter is 20 nm to 1000 nm, and the length is 2 μm to 100 μm. The diameter is preferably 100 nm to 1000 nm, and the length is preferably 5 μm to 80 μm.

[0036] In some embodiments, the high wettability polymer nanofibers are high wettability polyimide fibers, and the monomers containing electrophilic electrolyte groups for synthesizing polyimide include but are not limited to: at least one of 3,5'-diaminobenzoic acid, bis(3-amino-4-hydroxyphenyl)sulfone, 9,9-bis(3-amino-4-hydroxyphenyl)fluorene, 4,4'-diaminobiphenyl-2,2'-dicarboxylic acid, 2,2-bis(3-amino-4-hydroxyphenyl)hexafluoropropane, 3,3'-dihydroxybenzidine, diphenylphosphoric dianhydride, 1,2,4,5-benzenetetracarboxylic dianhydride, 4,4'-dicyanodiphenyl diamine, 4,4'-diimidazole diphenyl ether (ImDA), and 4,4'-diaminodiphenylmethane (MDA).

[0037] In the dispersant aqueous solution preparation step S11, the dispersant comprises at least one of polyethylene, polyethylene glycol, sodium polyacrylate, ammonium polyacrylate, and sodium hexametaphosphate. In some embodiments, the mass ratio of the dispersant to the dispersant aqueous solution is 1: (50 to 2000), that is, 0.05% to 2%. In the fiber powder aqueous solution formation step S12, the weight ratio of the high wettability polymer nanofiber and the ceramic powder is (1 to 40): (99 to 60); preferably (3 to 30): (97 to 70). The cost of high wettability polymer nanofibers is much higher than that of ceramic powders, and the content of nanofiber powder is too high, which is not conducive to reducing the cost of large-scale production. In some embodiments, the total solid content of ceramic powder and high wettability polymer nanofibers in the fiber powder aqueous solution is 20wt% to 50wt%. In the coating slurry preparation step S13, the thickener comprises at least one of sodium carboxymethyl cellulose, methyl cellulose, hydroxypropyl methyl cellulose, and carbo resin. In some embodiments, the total mass ratio of the thickener to the solid fiber powder (i.e., the high wettability polymer nanofibers and ceramic powder) is (0.1 to 2): 100. In the coating slurry preparation step S13, the wetting agent comprises at least one of organic modified silicon oxides, polyols, and fatty alcohol ethers. In some embodiments, the total mass ratio of the wetting agent to the solid fiber powder (i.e., the high wettability polymer nanofibers and ceramic powder) is (0.1 to 5): 100.

[0038] In some embodiments, the coating method of the slurry coating step S14 is one of gravure printing, doctor blade coating, extrusion coating, and wire rod coating; the coating position is any one side or both sides of the base film. Optionally, in the slurry coating step S14, the base film coated with the coating slurry is dried. The drying method is preferably drying. The drying temperature is 40°C to 150°C; the time is 0.05h to 0.5h.

[0039] In the invention, some parameters are designed to conduct experiments, and the experimental process and results are summarized as follows.

[0040] Example 1

[0041] This embodiment provides a high wettability fiber composite battery separator, and the preparation method thereof is as follows:

[0042] Step 1: 3,3'-dihydroxybenzidine and diphenylphosphoric acid dianhydride monomers are selected for polycondensation reaction in DMF solvent to generate a polyamic acid solution. The fibers obtained by the spinning method are subjected to imidization treatment at 300°C, and finally ground by a grinding homogenizer for 30 minutes to obtain high-wet short fibers with a diameter of 100nm to 500nm and a length of 5μm to 60μm.

[0043] Step 2: Weigh 0.5 g of sodium polyacrylate and dissolve it in 150 g of deionized water. Use a magnetic stirrer to stir at 500 r / min for 6 hours to form a dispersant aqueous solution.

[0044] Step 3: 98 g of alumina powder and 2 g of high wettability polyimide nanofibers were added to the aqueous dispersant solution, stirred at 500 r / min using a magnetic stirrer for 1 h, and then ground.

[0045] Step 4: Add 10g of sodium carboxymethyl cellulose aqueous solution, stir for 30 minutes, then add 20g of acrylate emulsion, stir for 1 hour using a magnetic stirrer at 300r / min, add 0.05g of silicone surface additive after uniform dispersion, and stir for 12 hours using a magnetic stirrer at 300r / min to obtain a uniform slurry.

[0046] Step 5: Use a coating machine to apply the slurry to one side of a polyethylene film with a thickness of 7 μm, dry it in an oven at 60°C for 30 min, and after drying, the coating thickness is 2 μm to obtain a single-sided coated separator.

[0047] Example 2

[0048] This embodiment provides a method for preparing a high wettability fiber composite battery separator. The difference between this embodiment and Example 1 is that the masses of the alumina powder and the high wettability polyimide fiber in step 3 are 94 g and 6 g.

[0049] Example 3

[0050] This embodiment provides a method for preparing a high wettability fiber composite battery separator. The difference between this embodiment and Example 1 is that in step 3, the masses of the alumina powder and the high wettability polyimide fiber are 90 g and 10 g, respectively.

[0051] Example 4

[0052] This embodiment provides a method for preparing a high wettability fiber composite battery separator. The difference between this embodiment and Example 1 is that in step 3, the masses of the alumina powder and the high wettability polyimide fiber are 86 g and 14 g, respectively.

[0053] Comparative Example 1

[0054] Uncoated base film.

[0055] Comparative Example 2

[0056] In order to compare the effect of high wettability polyimide fibers on improving the wettability of the diaphragm, the difference between this example and Example 1 is that only 100 g of alumina powder is added in step 3.

[0057] 2. Performance Test

[0058] [Contact angle test]

[0059] Test method: Lay the test surface of the diaphragm sample flat on a glass slide to ensure that there are no wrinkles. Use a contact angle meter to test. Adjust the sample stage to a horizontal level, place the sample on the stage, collect the sample background, start dripping, the drip volume is 2.0μL, adjust the baseline, and read the left and right angle values.

[0060] [Wettability test]

[0061] Test method: Cut the membrane into samples with L*W=50mm*50mm, mark the MD and TD directions, lay the membrane flat on the slide, and fix the four corners with green tape. Place the sample on the sample table (with horizontal and vertical table patterns for reference), set the test conditions: volume 2.0μL, drop medium, take a photo through a microscope immediately after dropping, take a photo again after 5 minutes, mark the radius dimensions S1 and S2 of the area of ​​the membrane immersed in the liquid before and after, and calculate the value of S2-S1.

[0062] [Moisture test]

[0063] Test method: accurately weigh about 0.1g to 0.2g of the sample on an electronic balance, and heat it at a set heating temperature of 150℃ for 5 minutes. Use a Karl Fischer tester for testing, reagent information: 1.09257, solvent is methanol; pH = 5.5; test pre-equilibrium critical point: drift value ≤ 5μg / min; test pre-equilibrium time: stable for 40s.

[0064] [Battery cycle capacity test]

[0065] Test method: Use a 86mm wide diaphragm to make a soft-pack battery cell. Cycle it at 1C for 1000 times at a temperature of 25℃±2℃, and record the battery cycle capacity retention rate.

[0066] The coated diaphragms prepared in Examples 1 to 4 and Comparative Examples 1 to 2 were tested for performance, and the test results are shown in Table 1 below:

[0067] Table 1

[0068]

[0069] According to Table 1: By comparing Examples 1 to 4, it can be found that as the mass ratio of the high wettability polyimide fiber increases, the wettability is enhanced, and the battery cycle capacity retention rate also increases accordingly. When the mass ratio of the high wettability polyimide fiber to the alumina powder in Example 3 and 4 and Example 4 reaches 14:86, its wettability is not significantly improved, and the moisture content is increased, resulting in a decrease in the battery cycle capacity retention rate and an increase in production costs.

[0070] By comparing Example 3 with Comparative Examples 1 and 2, it can be found that the addition of high wettability polyimide fibers can significantly improve the wettability of the separator. In summary, the high wettability polyimide fibers in the coating can effectively improve the wettability, thereby improving the cycle capacity retention performance of the battery.

[0071] The present application provides a high wettability fiber composite battery separator and preparation method, which has at least the following gain effects: in the separator coating, the high wettability nanofibers and ceramic powders are evenly mixed in a certain proportion to form a fiber-ceramic mixture. The mixing ratio is adjusted according to specific needs and experimental optimization. While ensuring that the ceramic powder with high chemical stability and high mechanical strength can enhance the structural strength of the separator coating, the wettability fiber with low surface energy and good affinity with the electrolyte can effectively increase the wettability and contact area between the electrolyte and the separator coating, thereby improving the ion transmission efficiency of the battery and further improving the battery performance.

[0072] The above contents involving common knowledge are not described in detail, and those skilled in the art can understand them.

[0073] The phrase "in some embodiments" and "in various embodiments" is used repeatedly. The phrase generally does not refer to the same embodiment; however, it may refer to the same embodiment. The words "including," "having," and "comprising" are synonymous unless the context indicates otherwise.

[0074] The above description is only an embodiment of the present application and does not constitute any form of limitation to the present application. Although the present application has been disclosed as above with specific embodiments, it is not intended to limit the present application. Any technician familiar with the profession can make slight changes or modifications to equivalent embodiments of equivalent changes using the technical contents disclosed above without departing from the scope of the technical solution of the present application. However, any simple modification, equivalent changes and modifications made to the above embodiments based on the technical essence of the present application without departing from the content of the technical solution of the present application are still within the scope of the technical solution of the present application.

Claims

1. A high wettability fiber composite battery separator, characterized in that: The composite battery separator includes a base film and a coating, wherein the coating is applied on one side or both sides of the base film; the coating contains high wettability polymer nanofibers, ceramic powder and a binder, and its single-side thickness is 0.5μm to 4μm; the high wettability polymer nanofibers have polar functional groups, and the binder fixes the ceramic powder and the high wettability nanofibers on the base film; the base film includes at least one of a polyethylene microporous membrane, a polypropylene microporous membrane, and a polypropylene / polyethylene composite microporous membrane, and its thickness is 3μm to 20μm.

2. The high wettability fiber composite battery separator according to claim 1, characterized in that: The coating comprises a single layer or a double layer, wherein the high wettability polymer nanofibers, the ceramic powder and the binder contained in each layer are the same or different.

3. The high wettability fiber composite battery separator according to claim 1, characterized in that: The high wettability polymer nanofiber includes at least one of aramid fiber, polytetrafluoroethylene fiber, polyimide fiber, cellulose nanofiber, and polyacrylonitrile nanofiber.

4. The high wettability fiber composite battery separator according to claim 1, characterized in that: The high wettability polymer nanofiber has a diameter of 20 nm to 1000 nm and a length of 2 μm to 100 μm.

5. The high wettability fiber composite battery separator according to claim 1, characterized in that: The high wettability polymer nanofiber has an aspect ratio of 2 to 5,000.

6. The high wettability fiber composite battery separator according to claim 1, characterized in that: The ceramic powder includes at least one of aluminum oxide, boehmite, barium titanate, barium sulfate, silicon dioxide, titanium dioxide, magnesium oxide, aluminum hydroxide, magnesium hydroxide, silicon nitride, and silicon carbide.

7. The high wettability fiber composite battery separator according to claim 1, characterized in that: The particle size D50 of the ceramic powder is 0.05 μm to 3 μm.

8. The high wettability fiber composite battery separator according to claim 1, characterized in that: The high wettability polymer nanofiber contains at least one of a cyano group (-CN), an ester group (-COOR), an ether group (-OR), a carboxyl group (-COOH), an amino group (-NH2), a sulfonic acid group (-SO3H), an acetyl group (-COCH3), a sulfonyl group (-SO2-), a pyridine group (-C5H5N), an aldehyde group (-CHO), a thienyl group (-C4H3S), a nitrile group (-C≡N), an alkoxy group (-OCH2-), and a phosphate group (-PO4), so that polar functional groups that are pro-electrolyte are formed on the surface of the high wettability nanofiber.

9. The high wettability fiber composite battery separator according to claim 1, characterized in that: The weight ratio of the high wettability polymer nanofibers to the ceramic powder is (1 to 40):(99 to 60).

10. The high wettability fiber composite battery separator according to claim 1, characterized in that: The binder includes at least one of polyvinylidene fluoride, polytetrafluoroethylene, polyvinyl alcohol, polyacrylic acid, polyacrylonitrile and polymethyl methacrylate.

11. A method for preparing a high wettability fiber composite battery separator, characterized in that: The following steps are involved: A dispersant aqueous solution preparation step: adding the dispersant into deionized water and stirring well to obtain the dispersant aqueous solution; A fiber powder aqueous solution forming step: adding high wettability polymer nanofibers and ceramic powder to the dispersant aqueous solution and continuing to stir, and then adding to a homogenizer for dispersion to obtain a fiber powder aqueous solution, wherein the high wettability polymer nanofibers have polar functional groups; A coating slurry preparation step: sequentially adding a binder, a thickener, and a wetting agent into the fiber powder aqueous solution, stirring evenly, and then performing demagnetization filtration to obtain the coating slurry; and A slurry coating step: coating the coating slurry on the base film, and then drying it to obtain a high wettability fiber composite battery separator.

12. The method for preparing a high wettability fiber composite battery separator according to claim 11, characterized in that: In the step of preparing the dispersant aqueous solution, the dispersant comprises at least one of polyethylene, polyethylene glycol, sodium polyacrylate, ammonium polyacrylate, and sodium hexametaphosphate.

13. The method for preparing a high wettability fiber composite battery separator according to claim 11, characterized in that: In the fiber powder aqueous solution forming step, the high wettability polymer nanofibers include at least one of aramid fibers, polytetrafluoroethylene fibers, polyimide fibers, cellulose nanofibers, and polyacrylonitrile nanofibers.

14. The method for preparing a high wettability fiber composite battery separator according to claim 11, characterized in that: In the fiber powder aqueous solution forming step, the ceramic powder includes at least one of aluminum oxide, boehmite, barium titanate, barium sulfate, silicon dioxide, titanium dioxide, magnesium oxide, aluminum hydroxide, magnesium hydroxide, silicon nitride, and silicon carbide.

15. The method for preparing a high wettability fiber composite battery separator according to claim 11, characterized in that: In the fiber powder aqueous solution forming step, the total solid content of the ceramic powder and the high wettability polymer nanofibers in the fiber powder aqueous solution is 20 wt % to 50 wt %.

16. The method for preparing a high wettability fiber composite battery separator according to claim 11, characterized in that: In the coating slurry preparation step, the thickener comprises at least one of sodium carboxymethyl cellulose, methyl cellulose, hydroxypropyl methyl cellulose, and carbopol resin.

17. The method for preparing a high wettability fiber composite battery separator according to claim 11, characterized in that: In the coating slurry preparation step, the wetting agent includes at least one of organically modified silicones, polyols, and fatty alcohol ethers.

18. The method for preparing a high wettability fiber composite battery separator according to claim 11, characterized in that: In the coating slurry preparation step, the binder includes at least one of polyvinylidene fluoride, polytetrafluoroethylene, polyvinyl alcohol, polyacrylic acid, polyacrylonitrile, and polymethyl methacrylate.

Citation Information

Cited By

  • Lithium ion battery diaphragm with high heat resistance and high ionic conductivity and preparation method thereof

    CN120149733A

  • Battery separator and electrochemical device comprising same

    WO2026179359A1